Protection of trade marks in the EC - Grubhofer, Gregor (My University, 2003)
Bu çalışmada; markaların bir bölümünü oluşturduğu sınai mülkiyet haklarının tanımını vermek suretiyle konunun kısa bir açıklaması ve tarihi gelişimleri sürecinde markaların kullanım amaçlarına dair açıklama yapılmıştır. Bunu müteakip, Avrupa Birliği hukuku çerçevesinde, konuyla ilgili en önemli uluslararası anlaşmalardan bahsedilmiştir. Konunun esasına giriş; Avrupa Adalet Divanının, malların serbest dolaşımı ve bunun ulusal marka kanunları üzerindeki etkisine dair ilk kararlarının açıklaması ile yapılacaktır. Marka hukuku konusunda Avrupa Birliği'nin yetkisi, malların paralel ithali ve hakların tüketilmesi doktrini bu bölümdeki ilgili konulardan birkaçıdır. Markalara ilişkin hakların lisans konusu yapılması, Avrupa Birliği dahilinde adil rekabete ilişkin kurallara dair olan bir sonraki bölümün konusunu oluşturmaktadır. Çalışmanın sonraki kısımlarında, üye devletlerin marka kanunlarının uyumlaştırılmasına dair EEC/ 89/ 104 Yönergesi incelenmektedir. Avrupa Adalet Divanının en son kararları ışığındaki en son gelişmeler bu bölümde açıklanmaktadır. En son olarak, Topluluk Markasının ihdasına dair EC/ 40/ 94 Yönetmeliği, son bölümün konusunu oluşturmaktadır. Bu, markaların ulusal bazda tesciline, tüm topluluk bölgesinde yeknesak koruma sağlayarak bir alternatif oluşturmaktadır.

The study comprises a brief explanation of the subject by defining intellectual property of which trade marks are a part of and will explain the function of trade marks on the background of their historical development. In the following the most important international agreements that are related to this subject are introduced and explained in the context of European Community Law. The main subject will start with the early case law of the European Court of Justice, in which the provisions providing for free movement of goods and their impact on national trade mark laws will be explained. The competence of the European Community in the field of trade mark laws, parallel importation of goods and the exhaustion of rights doctrine will be some of the related matters in this chapter. The licensing of rights related to trade marks are then subject of the following chapter which deals with those rules that shall provide fair competition within the European Community. The following part of the studies will scrutinize Directive 89/ 104/ EEC concerning the approximation of trade mark laws in the Member States. On the base of recent case law of the ECJ the latest developments will be explained in this chapter. Finally, Regulation 40/ 94/ EC regarding the introduction of a Community Trademark is going to form the subject of the last chapter, which will present an option to the national registration of trade marks by providing uniform protection throughout the entire area of the Community.
Keywords: Ticari Markalar_Avrupa Topluluğu Ülkeleri